TINJAUAN POLITIK DALAM PROGRAM MAKAN BERGIZI GRATIS ( STUDI PADA SISWA SEKOLAH DASAR KOTA PALEMBANG)TINJAUAN POLITIK DALAM PROGRAM MAKAN BERGIZI GRATIS ( STUDI PADA SISWA SEKOLAH DASAR KOTA PALEMBANG) - Nabila, Siti Zaitun; Juainah, Norma; Afriany, Deany (PRAJA: Jurnal Ilmiah Pemerintahan, 2026)
The implementation of the Free Nutritious Meals Program (MBG) in elementary schools is a government effort to improve welfare and the quality of education by meeting students' nutritional needs. This study aims to analyze the political review of the implementation of the free nutritious meal program for elementary school students in Palembang and to identify and explain the impact of the implementation of the free nutritious meal program. The theory used by the researcher is the theory of political development explained by Warjio, which states that development is never neutral but is a political process involving various actors, interests, strategies, and powers. This study uses qualitative methods with data collection techniques through observation, interviews, and documentation. The results show that the implementation of the Free Nutritious Meal Program (MBG) in elementary schools in Palembang City reflects the involvement of political actors in public policy, in accordance with development politics theory. The local government, through collaboration with the Education Office, Health Office, SPPG, and schools, demonstrates synergy in the implementation of the program. The democratic political system is evident in the cross-sectoral coordination through MoUs that are responsive to community needs. Ideologically, the program is based on the values of social justice and equitable welfare. This program is purely a domestic policy without foreign financial intervention, although there is international technical assistance. The development process is carried out participatively through planning, data collection, and evaluation. Strategically, the program strengthens the image of the local government as caring for the welfare of the community. Positive impacts are seen in increased enthusiasm for learning, togetherness, and reduced economic burdens on families, although they are not yet significant in terms of health and intelligence and still face technical obstacles such as disruption to learning time.